Editorial: Comparative Education and (De)Colonial Entanglements: Towards More Sustainable and Equitable Learning Futures - Fischman, Gustavo E.; Silova, Iveta (Revista Española de Educación Comparada, 2023)
The last several decades have seen a global resurgence of academic engagement with decolonial, postcolonial, anti-colonial, and southern scholarship as a way to confront the persisting modern/colonial legacies in education. This special issue brings together a collection of nine articles to critically interrogate (de)colonial entanglements in comparative education by addressing three questions. Who benefits from and who is punished by the colonial legacies of knowledge production in comparative education? How can the professionals and scholars in the field generate more sustainable and just (trans)local and multilingual research practices that act as epistemic disobedience against coloniality? How might we learn from this uncertain time to construct new comparative genres that extend beyond the Western modern/colonial logic? The articles in this special issue challenge the current preoccupation of many researchers, educators, and policy-makers with global education trends – student achievement tests, competitive education league tables, global ranking exercises, and “best practices”– inviting comparative education researchers to articulate decolonial, antisexist, antiracist, and regenerative alternatives that recognize the interdependence of people, place, and planet, as well as the importance of cultural change. Collectively, this special issue aims at creating a space for welcoming critical and creative scholarship to radically reimagine – and ultimately transform – education for more sustainable and equitable global futures.